ANALISIS DAMPAK PENGGUNAAN FAKTOR PRODUKSI TERHADAP PRODUKSI PADI SAWAH PADA MODEL PEMBANGUNAN PERTANIAN BERBASIS LOKAL (MPPBL) DAN MANFAAT EKONOMINYA BAGI MASYARAKAT - AGUSTONO AGUSTONO (Universitas Sebelas Maret, 2010)
The goal of analysis are (1) to understand of impact from the MPPBL to increase of the rice production; (2) to understand of influence and production elasticity from production factors in the MPPBL and the non MPPBL; and (3) to account of the economic benefit for society of the MPPBL.